Severe depression - McIntyre, Roger S.; Nathanson, Jay. (New York : Oxford University Press, 2010)
Major depressive disorder is highly prevalent, recurrent, and associated with inter-episodic dysfunction. This book focuses on current treatment strategies as well as an algorithmic approach to selecting and sequencing therapies for individuals with severe depression. Novel systematic approaches as well as psychosocial strategies are also reviewed.
Description based on print version record.
Includes index.
Keywords: Depression, Mental